Genetic factors of idiopathic central precocious puberty and their polygenic risk in early puberty. Issue 4 (27th August 2021) - Lin, Wei-De; Cheng, Chi-Fung; Wang, Chung-Hsing; Liang, Wen-Miin; Chen, Chien-Hsiun; Hsieh, Ai-Ru; Chiu, Mu-Lin; Lin, Ting-Hsu; Liao, Chiu-Chu; Huang, Shao-Mei; Tsai, Chang-Hai; Chang, Cherry Yin-Yi; et al.
Abstract: Objective: To investigate the genetic characteristics of idiopathic central precocious puberty (ICPP) and validate its polygenic risk for early puberty. Design and methods: A bootstrap subsampling and genome-wide association study were performed on Taiwanese Han Chinese girls comprising 321 ICPP patients and 148 controls. Using previous GWAS data on pubertal timing, a replication study was performed. A validation group was also investigated for the weighted polygenic risk score (wPRS) of the risk of early puberty. Results: A total of 105 SNPs for the risk of ICPP were identified, of which 22 yielded an area under the receiver operating characteristic curve of 0.713 for the risk of early puberty in the validation group. A replication study showed that 33 SNPs from previous GWAS data of pubertal timing were associated with the risk of ICPP (training group: P -value < 0.05). In the validation group, a cumulative effect was observed between the wPRS and the risk of early puberty in a dose-dependent manner (validation group: Cochran–Armitage trend test: P -value < 1.00E−04; wPRS quartile 2 (Q2) (odds ratio (OR) = 5.00, 95% CI: 1.55–16.16), and wPRS Q3 (OR = 11.67, 95% CI: 2.44–55.83)). Conclusions: This study reveals the ICPP genetic characteristics with 22 independent and 33 reported SNPs in the Han Chinese population from Taiwan. This study may contribute to understand the genetic features and underlying biological pathways that control pubertal timing and pathogenesis of ICPP and also to the identification of individuals with a potential genetic risk of early puberty.